Urte guztiak dire diferente : narratiba 1984 / [zenbait egile, Mikel Antza ... et al.] - Antza, Mikel; Utretx, Roman; Mendiguren Elizegi, Xabier; Lizarralde, Pello; Uria, Iñaki; Setien, Gorka (1958-2024); Iñurrieta, Iñaki; Olasagasti, Eneko (Susa 83-86, 1983)
Mikel Antza, Roman Utretx, Xabier Mendiguren, Pello Lizarralde, Iñaki Uria, Gorka Setien, Iñaki Iñurrieta eta Eneko Olasagastiren ipuinak jasotzen dira liburu honetan